Феномен булінгу в контексті соціалізації особистості - Юхименко, Наталія; Yukhymenko, Nataliia (Волинський національний університет імені Лесі Українки, 2020)
У статті здійснено спробу аналізу «булінгу» як соціально-філософського феномену. Визначено, що молоде покоління транслює саме ті цінності, які формуються через взаємодію із середовищем, суспільством, у якому воно зростає. Ціннісні орієнтації особистості охарактеризовано як елементи внутрішньої (диспозиційної) структури особистості, що сформовані та закріплені життєвим досвідом індивіда в процесі соціалізації. А становлення особистісного в дитині передбачає засвоєння нею системи суспільних цінностей. Булінг розглянуто як один із факторів розкриття ієрархічних відносин особистості й соціуму в процесі соціалізації, персоналізації та самоідентифікації. Булінг визначено як цькування через насилля в процесі персоналізації.

The article attempts to analyze the category of «bullying» as a socio-philosophical phenomenon. It is determined that the young generation broadcasts exactly the values that are formed through interaction with the environment, the society in which it grows up. Personality value orientations are characterized as elements of the internal (dispositional) structure of personality, formed and consolidated by the life experience of the individual in the process of socialization. And the formation of personality in a child involves assimilation of the system of social values. It is shown that every personality has a deep need for personalization, which is the basis for communication and interaction between people, being realized in joint activities. That the personality continues itself in other personalities, «broadcasting» its individuality to others. The ability to personalization is provided by the richness of personality, the variety of means by which it can in communica-tion and activity to make an impact. It is proved that, on the one hand, the personality in the process of its formation, identifying and endowing itself with certain traits and characteristics, absorbing experience and forming its own hierarchy of values, is capable of violence, because it chooses it as an element of interaction in an environment whose values are close and related, and on the other hand, is a relay of society, which is close and related to it and through manifestations of violence as well. Bullying is considered as one of the factors of revealing the hierarchical relationship between the individual and society in the process of socialization, personalization and self-identification. Bullying is defined as bullying through violence in the process of personalization.
The Phenomenon of Bullying in the Context of Personality Socialization
Keywords: особистість; соціалізація; персоналізація; самоідентифікація; булінг; становлення особистості; personality; socialization; personalization; self-identification; bullying; personality formation; 316.613.434:177.8